TEATER LENONG SEBAGAI IDENTITAS BUDAYA BETAWI (Studi Kasus di Sanggar Cahaya Timur, Ciracas, Jakarta Timur) - Abdullah, Della Agyta; Fateghipon, Abdul Haris (Edukasi IPS, 2018)
This research purpose to knowing about characteristics of, the process of socializing the revitalization of Lenong theater. This research uses a qualitative approach. Data techniques used are semi-structured interviews, interviews and field notes. The results of this study conclude first, Lenong theater arts have characteristics or elements that characterize that art is lenong. These characteristics are the accompaniment of the lenong theater, martial arts at the lenong theater . Lenong theater stories, lenong costume, lenong theater language. religion which shows that the Betawi people are Muslims. Second, socialization of Lenong theater is influenced by two factors, namely supporting factors and inhibiting factors. Supporting factors, namely the personal approach means that Lenong theater is usually performed at weddings and circumcisions, and the group approach means that Lenong theater is also performed at performances, cultural festivals, and also the birthday of DKI Jakarta. The inhibiting factor is the limited space for displaying lenong theater, the cost of treating lenong which is expensive and the development of Jakarta's society which is increasingly a global lifestyle. Third, the revitalization of Lenong theater is by means of education, information technology, various shows in tourist attractions and television stations